Political Feasibility and Investment in Economic Transformations - Isard, Peter (IMF Working Papers; Working Paper ;, 1993)
The paper characterizes the feasibility of economic transformation as requiring the simultaneous attainment of macroeconomic stability, political support, and adequate private investment. Macroeconomic stability is defined as fiscal balance; political feasibility is related to the income gains and losses of different population groups; and private investment is linked to public 'infrastructure' investment. The analysis illustrates that attainment of the multiple requirements for successful transformation may necessitate a 'big push' with external financial and technical assistance. It also emphasizes the importance of the productivity gains achieved when workers are induced to make occupational choices consistent with their comparative advantages.